Design tool in T&L: RC retaining wall / Mohamad Irwan P. Harahap and Felix Ling - P. Harahap, Mohamad Irwan; Ling, Felix (2020)
The economic booms experienced by Malaysia in recent times has propelled the construction industry as never before to serve the growing needs for structural and infrastructural developments. Myriad of projects with differing scales, complexity and market expectations have been taunting practitioners and academicians in the technical compass for years. This is further compounded by restrictive land constraints pushing developments ever towards more challenging topographies. As a result, unexpected and undesirable work outcomes would inadvertently come to the fore in the form of sub-standard or even failed products. Not too uncommon would we be served with news of retaining wall failures leading to massive property damages and potential loss of lives. Conventional practices are either inflexible or not customizable to local practices. This innovation develops an Excel VBA-based program that could facilitate the analysis and design processes of a reinforced concrete (RC) retaining wall based on the con-current design standard namely Eurocode 2. It employs an array of programmable functionalities such as alphanumeric entries and graphical displays to allow for flexibility as well as intuitive usage over ubiquitous platform. Both practitioners and academicians would benefit from resulting computational accuracies and resolved intricacies at a fraction of the cost and time.